Determination of ROE, DER, and EPS on Stock Prices: A Study on State-Owned Banks On The Indonesia Stock Exchange - Hisnol Jamali; Haeruddin, Haeruddin (Al-Buhuts, 2024)
T This study aims to analyze the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), and Earning Per Share (EPS) on the Stock Price of companies listed on the Indonesia Stock Exchange. The research method uses panel data regression with the Fixed Effects Model approach and the Hausman Test to determine the most appropriate model. The findings show that ROE has a negative but not significant effect on the Stock Price, while DER has a negative and significant effect, and EPS has a positive and significant effect on the Stock Price. This research contributes by emphasizing the importance of EPS in investment valuation as well as the need to manage DER carefully. The implication of this result is that investors should pay more attention to EPS in investment decisions, while companies are advised to focus on improving EPS and DER management. The study is limited to data for a specific period and a small number of companies, which can affect the generalization of results. his study aims to analyze the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), and Earning Per Share (EPS) on the Stock Price of companies listed on the Indonesia Stock Exchange. The research method uses panel data regression with the Fixed Effects Model approach and the Hausman Test to determine the most appropriate model. The findings show that ROE has a negative but not significant effect on the Stock Price, while DER has a negative and significant effect, and EPS has a positive and significant effect on the Stock Price. This research contributes by emphasizing the importance of EPS in investment valuation as well as the need to manage DER carefully. The implication of this result is that investors should pay more attention to EPS in investment decisions, while companies are advised to focus on improving EPS and DER management. The study is limited to data for a specific period and a small number of companies, which can affect the generalization of results.